PERILAKU SEKSUAL PACARAN REMAJA DI WILAYAH PUSKESMAS MAGELANG TENGAH - Prisca Dama Shinta; Zahroh Shaluhiyah; Besar Tirto Husodo; Bagoes Widjanarko (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2015)
Data from the city of health department clinics Magelang and 5 health centres in the city of Magelang , the number of cases of unwanted pregnancies in adolescents in the region of Central Magelang in Magelang health center tends to increase from year to year compared to other health centers in the city of Magelang. The types of sexual behavior are touching, kissing, necking, petting, intercourse. The purpose of this study was to analyze the relationship between the variables of sexual behavior in dating. The purpose of this study is to analyze the relationship between the characteristics of respondents , knowledge , attitudes , accessible media , friends attitudes , behaviors friends , and family upbringing respondents' sexual behavior in courtship . The method used quantitative cross-sectional approach . The population is adolescents in Central Magelang Puskesmas with a sample of the 49 respondents . Analysis of the data using univariate and bivariate analysis with the chi-square statistical test . Respondents aged < 17 years ( 38.1 % ) and ≥ 17 years ( 71.4 % ) . All respondents were female . Respondents with good knowledge ( 61.2 % ) , non permissive respondents of sexual behavior ( 91.8 % ) , accessing media on pornography ( 36.7 % ) , non permissive attitude respondent’s friend of sexual behavior ( 83.7 % ) , permissive respondent’s friend of sexual behavior ( 55.1 % ) , Pattern foster families ( 59.2 % ) . Chi Square test results found no relationship between the behavior of a friend with sexual behavior in the courtship of respondents . So from the results of these studies suggested the support of health authorities and health centers in providing extension sekual in courtship behavior that can be at risk of unwanted pregnancy.